Carbon stock analysis of some cocoa planting systems in South Sulawesi. Issue 1 (April 2020) - Mustari, K; Asrul, L; Kaimuddin,; Faradilla, L
Abstract: In an effort to control carbon emissions in the air, steps taken are improving forest vegetation and protecting natural forest vegetation as the biggest absorber of carbon gas emissions. Cocoa as the largest plantation crop in Indonesia is expected to be able to absorb CO2 gas emissions in the air due to its ability to absorb carbon. A carbon analysis study was carried out on cacao plantation to determine the level of carbon uptake in each cropping system in South Sulawesi. Hence, the results of the analysis can be a reference in climate change mitigation efforts. Three regencies, each with 3 districts were selected as study locations, namely East Luwu Regency (Burau, Wotu and Mumpangana Districts), Pinrang Regency (Patampanua, Batulappa and Lembang Districts), and Bantaeng Regency (Gantarangkeke, Tompobulu, and Eremerasa Districts). Carbon stored measurements was conducted using allometric formula. Measurements were carried out on 200 m 2 observation plot. Results show that carbon sequestration levels were 33.19 tons C/Ha, 25.52 tons C/Ha, 32.07 tons C/Ha in East Luwu, Pinrang and Bantaeng regencies, respectively. The amount of carbon emissions absorbed in East Luwu Regency was 57.46 t/Ha, Pinrang Regency 67.12 t/Ha, and Bantaeng Regency 60.07 t/Ha. The CO2 content based on the composition of land cover in East Luwu Regency was 121.81 tons CO2 /Ha, Pinrang Regency 93.69 tons CO2 /Ha, and Bantaeng Regency 117.70 tons CO2 /Ha.